2004
DOI: 10.1161/01.cir.0000131860.80444.ab
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Potentiates Angiotensin II–Induced Signaling in Vascular Smooth Muscle Cells

Abstract: Background-In a double-transgenic human renin and human angiotensinogen rat model, we found that mineralocorticoid receptor (MR) blockade ameliorated angiotensin II (Ang II)-induced renal and cardiac damage. How Ang II and aldosterone (Ald) might interact is ill defined. Methods and Results-We investigated the effects of Ang II (10 Ϫ7 mol/L) and Ald (10 Ϫ7 mol/L) on extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) signaling in vascular smooth muscle cells (VSMCs) with Western blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
172
0
5

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(191 citation statements)
references
References 44 publications
14
172
0
5
Order By: Relevance
“…In various animal models of renal diseases, aldosterone is involved in endothelial dysfunction, inflammation, proteinuria, and fibrosis (48). Aldosterone increases the effect of AngII, induces the generation of reactive oxygen species, and leads to an acceleration of the AngII-induced activation of mitogenactivated protein kinases (49). These findings indicate that blockade of mineralocorticoid receptors presumably is beneficial even in situations with high AngII, because common signal transduction pathways between the two systems are interrupted.…”
Section: What About Aldosterone?mentioning
confidence: 99%
“…In various animal models of renal diseases, aldosterone is involved in endothelial dysfunction, inflammation, proteinuria, and fibrosis (48). Aldosterone increases the effect of AngII, induces the generation of reactive oxygen species, and leads to an acceleration of the AngII-induced activation of mitogenactivated protein kinases (49). These findings indicate that blockade of mineralocorticoid receptors presumably is beneficial even in situations with high AngII, because common signal transduction pathways between the two systems are interrupted.…”
Section: What About Aldosterone?mentioning
confidence: 99%
“…These results suggest that aldosterone exerts a mitogenic effect synergistic with Ang II and that blockade of both MR and Ang II may provide enhanced protection from vascular remodeling, as already reported by Iglarz et al 56 Ang II and aldosterone stimulate MAP kinase and ROS signaling. 47,55 Jaffe and Mendelsohn 57 showed that Ang II directly activates MRs in human coronary and aortic VSMCs (Figure 2). The presence of 11-␤-hydroxysteroiddehydrogenase-2, necessary for mineralocorticoid action, was also demonstrated.…”
Section: Schiffrinmentioning
confidence: 99%
“…Recently, it has been shown that the MAPK/ERK stress pathway is redox sensitive. [39][40][41] To determine whether the increase in ERK1/2 phosphorylation and activation is a consequence of oxidative stress, we treated Atm À/À astrocytes with antioxidant N-acetylcyste (NAC). The activation of ERK1/2 in these astrocytes was suppressed by treatment with NAC (38% reduction for ERK1 and 36% reduction for ERK2, Figure 3d).…”
Section: Atm Deficiency Induces Redox-sensitive Erk1/2 Phosphorylatiomentioning
confidence: 99%